KEPUASAN, LOYALITAS KONSUMEN DAN STRATEGI PENGEMBANGAN AGROINDUSTRI KERUPUK BAWANG DI KOTA BANDAR LAMPUNG - Nurul Fajri Indah Lestari; Dyah Aring Hepiana Lestari; Ani Suryani (Lampung University, 2020)
This research aims to analyze the level of satisfaction and loyalty of consumers’of onion crackers and build strategies on the development of onion creackers agroindustry in Bandar Lampung city . This research is a case study. The samples are stakeholders from agroindustry, government officer, employees, and consumers of onion crackers. Technique sampling for consumers is snowballing. The methods of data analysis used are Customer Satisfaction Index analysis(CSI) analysis, SWOT analysis and Quantitive Strategic Planing Matrix analysis (QSPM). The results of this research showed that onion crackers consumers were loyal customers with high levels of satisfaction (CSI = 71.04%) and on the loyalty pyramid consumers were categorized as loyal, because 63.33% of them were committed buyers. For strategies combination IFE value was 2.686 and EFE was 2.645. In the internal and external matrix the position of the business was in quadrant V, meaning that agroindustry were in the growth phase. Based on QSPM analysis, the recommended strategies were to increase the production amount especially in dry season in order to meet consumer demand in rainy season by implementing the provided production machines which were owned by the agroindustry.Key words: consumer, loyalty, onion crackers, statisfaction, strategy.